Interatrial conduction block with retrograde activation of the left atrium and paroxysmal supraventricular tachyarrhythmias: influence of preventive antiarrhythmic treatment. - Bayés de Luna, A.; Oter, M.C.; Guindo, J. (Elsevier, 1989)
Patients with advanced interatrial conduction block with retrograde activation to the left atrium present a high incidence of supraventricular tachyarrhythmias. We report the value of preventive antiarrhythmic treatment in these patients.